Enhancing maternal self-efficacy through infant massage: A randomized clinical trial among mothers of preterm infants - Pramitha, Dyan Ajeng; Hartanto, Fitri; Radityo, Adhie Nur; Sarosa, Gatot Irawan; Mellyana, Omega; Anam, Moh. Syarofil (Indonesian Pediatric Society, 2026)
Background: Preterm birth is a global health concern, often requiring Neonatal Intensive Care Unit (NICU) admission, which can lead to parent-infant separation. This separation may increase maternal stress and reduce caregiving confidence. Infant massage is a potential intervention to enhance maternal engagement and self-efficacy in caring for their premature infants. Objective: This study aims to evaluate the effect of infant massage on maternal self-efficacy in the care of preterm infants. Methods: This was a randomized controlled trial conducted at the NICU of Kariadi Hospital, Indonesia. A total of 56 mothers of preterm infants were randomly assigned to an intervention group (n=28) or a control group (n=28). Mothers in the intervention group were trained to perform infant massage for 5–10 minutes, twice daily, for seven consecutive days. The control group received standard care. Maternal self-efficacy was measured pre- and post-intervention using the Perceived Maternal Parenting Self-Efficacy (PMP S-E) questionnaire. Data were analyzed using the Wilcoxon signed-rank test. Result: The intervention group showed a statistically significant increase in self-efficacy across all four domains: caretaking procedures (p=0.010), evoking behavior (p<0.001), reading behavior or signaling (p<0.001), and situational beliefs (p=0.002). In contrast, the control group only demonstrated significant improvement in two domains (evoking behavior and reading Behavior). Conclusion: Infant massage performed by mothers is an effective intervention to significantly improve the self-efficacy of mothers with preterm infants in the NICU. This practice can be recommended to support maternal well-being and foster parent-infant bonding during hospitalization. Keyword: infant massage, maternal self-efficacy, preterm infant